Combination treatment of radiofrequency ablation and peptide neoantigen vaccination: Promising modality for future cancer immunotherapy - Shou, Jiawei; Mo, Fan; Zhang, Shanshan; Lu, Lantian; Han, Ning; Liu, Liang; Qiu, Min; Li, Hongseng; Han, Weidong; Ma, Dongying; Guo, Xiaojie; Guo, Qianpeng; et al. (Frontiers in Immunology, 2022)
Background The safety and immunogenicity of a personalized neoantigen-based peptide vaccine, iNeo-Vac-P01, was reported previously in patients with a variety of cancer types. The current study investigated the synergistic effects of radiofrequency ablation (RFA) and neoantigen vaccination in cancer patients and tumor-bearing mice. Methods Twenty-eight cancer patients were enrolled in this study, including 10 patients who had received RFA treatment within 6 months before vaccination (Cohort 1), and 18 patients who had not (Cohort 2). Individualized neoantigen peptide vaccines were designed, manufactured, and subcutaneously administrated with GM-CSF as an adjuvant for all patients. Mouse models were employed to validate the synergistic efficacy of combination treatment of RFA and neoantigen vaccination. Results Longer median progression free survival (mPFS) and median overall survival (mOS) were observed in patients in Cohort 1 compared to patients in Cohort 2 (4.42 and 20.18 months vs. 2.82 and 10.94 months). The results of ex vivo IFN-γ ELISpot assay showed that patients in Cohort 1 had stronger neoantigen-specific immune responses at baseline and post vaccination. Mice receiving combination treatment of RFA and neoantigen vaccines displayed higher antitumor immune responses than mice receiving single modality. The combination of PD-1 blockage with RFA and neoantigen vaccines further enhanced the antitumor response in mice. Conclusion Neoantigen vaccination after local RFA treatment could improve the clinical and immune response among patients of different cancer types. The synergistic antitumor potentials of these two modalities were also validated in mice, and might be further enhanced by immune checkpoint inhibition. The mechanisms of their synergies require further investigation. Clinical trial registration https://clinicaltrials.gov/, identifier NCT03662815.